Relasi Adat dan Hukum Islam: Menelisik Akulturasi dan Kearifan Lokal dalam Masyarakat Gorontalo - Kasim, Dulsukmi; Samad, Musdelifa Abu (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
The acculturation between customary traditions and Islamic law in Gorontalo is so strong that the general public often finds it difficult to distinguish between original Islamic teachings and customs that have been Islamized. Some customs have been fully adopted into Islamic law, while others have undergone modifications and adjustments. This study aims to analyze how Islamic law and local customs interact within Gorontalo society and to identify the various forms of acculturation that have taken place. The focus of this research is to examine how customs influence the practice of Islamic law, both in aspects that remain stable and those that have undergone changes. The research employs a library research method by reviewing various sources, including classical Islamic texts, previous studies, and references on both Islamic law and Gorontalo’s customary traditions. This sociological approach enables an in-depth analysis of how Islamic legal concepts have transformed through their interaction with local customs. The findings reveal that in the realm of ibadah mahdhah—such as ablution (wudu), dry ablution (tayammum), ritual bathing (mandi wajib), prayer (shalat), almsgiving (zakat), fasting (puasa), pilgrimage (hajj), minor pilgrimage (umrah), and animal sacrifice (qurban)—Islamic law has remained stable despite interactions with local traditions. However, in other aspects, such as marriage, inheritance, and certain religious practices—including remembrance of God (zikir), recitation of the Qur’an, the call to prayer (azan), funeral rites, and Friday prayers—changes in their implementation have occurred due to customary influences. This acculturation process has shaped a distinctive pattern in the application of Islamic law, giving rise to two forms of local wisdom: value-based wisdom and the adaptation of Islamic legal practices through customary processes. The contribution of this study lies in its deeper understanding of how Islamic law adapts within a local cultural context. The findings are expected to serve as a foundation for the development of more contextual studies on Islamic law and as a reference for formulating legal policies that remain faithful to Islamic principles while accommodating local wisdom